Remediation of TSS and Ammonia in the Rubber Liquid Waste by the Filter Media and the Water Plants (Limmnocharis flava, Echinodorus palaefolius) For Live Fish Media - Lenggo M, Febrizki; Hasbi, M.; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research aims to understand capability of filter media with water plants(Limmnocharis flava, Echinodorus palaefolius) in remediation TSS and Ammoniacontent in the rubber liquid waste. It has conducted from Februari to April in PT.Riau Crumb Rubber Factory Pekanbaru. Sampling of TSS and ammonia weretaken in five point with interval every 10 days for 4 times and analyzed inLaboratory of the Departement of Public Works and then compare with Kep-51/MENLH/1995. Filter media have a capabilility in remediation TSS witheffectivenesses 89,58% and ammonia 89,58%. Filter media with water plantsLimmnocharis flava have a capabilility in remediation TSS with effectivenesses93,51% and ammonia 90,59%. Filter media with water plants Echinodoruspalaefoli have a capabilility in remediation TSS with effectivenesses 94,63% andammonia 92,09 %. And filter media with water plants Limmnocharis flava andEchinodorus palaefolius have a capabilility in remediation TSS witheffectivenesses 95,35% and ammonia 92,82%. Percentage of survival rate forcommon 100%. It’s compliance with quality standard and as good as for fish lifemedia.Keywords : Sand Filter, Phytoremediation, Remediation